The Spirit of Capitalism, Precautionary Savings, and Consumption - Luo, Yulei; Smith, William T.; Zou, Heng-Fu (2012)
Recent research has shown that the "spirit of capitalism"--a preference for wealth itself, in addition to consumption--has important implications for growth and asset pricing. This paper explores how the spirit of capitalism affects saving and consumption behavior. We demonstrate that the spirit of capitalism may reduce the importance of precautionary savings. It can also explain the excess sensitivity puzzle: the spirit of capitalism causes dramatic deviations from a random walk. It may also offer a partial explanation of the excess smoothness puzzle.